DECENTRALIZATION AS AN EFFECTIVE MECHANISM FOR REGULATING INVESTMENTS IN THE EU AND UKRAINE - Кірієнко, С. (SWorldJournal, 2025)
The article is devoted to the study of the European experience of attracting investments with the identification of trends and prospects for Ukraine in the context of decentralization of power. The factors of opportunities, advantages and risks of decentr